Creating a Standardized Process to Meet Core Measure Compliance. Issue 4 (October 2015) - Kwan, Sarah; Daniels, Melodie; Ryan, Lindsey; Fields, Willa
Abstract : A standardized process to improve compliance with venous thromboembolism prophylaxis and hospital-based inpatient psychiatric services Core Measures was developed, implemented, and evaluated by a clinical nurse specialist team. The use of a 1-page tool with the requirements and supporting evidence, combined with concurrent data and feedback, ensured success of improving compliance. The initial robust process of education and concurrent and retrospective review follow-up allowed for this process to be successful. Abstract : Supplemental Digital Content is Available in the Text.